DESIGN OF ELECTROSTATIC PRECIPITATOR (ESP) PROTOTYPE AS A SOLID PARTICLE CAPTURE DEVICE FOR WASTE INCINERATION CHIMNEY EXHAUST - Heru Nugroho; Sunaryo; Ahmad Fati’in (Clean Energy and Smart Technology, 2024)
The waste discarded by the community every day comes from agricultural activities, markets, households, entertainment, and industry. One form of waste is domestic waste, which originates from household waste. The increase in domestic waste goes hand in hand with the development of physical infrastructure and the expansion of adequate facilities and infrastructure. As a result of this pollution, environmental balance is disrupted. In this experiment, one method will be used to reduce or minimize environmental pollution, especially air pollution, by using an electrostatic precipitator as a tool to capture solid particles from exhaust gas in waste combustion smoke. It is expected to efficiently reduce the solid particle content in the exhaust gas from waste combustion. The electrostatic precipitator is an alternative for reducing environmental pollution, as it has high efficiency, reaching 98.4%, and can capture particles as small as 100 micrometers. The electrostatic precipitator works by capturing solid particles that pass through the particle charging area, which is at a high potential. The charging area provides high-speed electrons by ionizing molecules and particles in the exhaust gas from the smoke. The exhaust gas particles receive positive ions and become highly charged, allowing them to be attracted and captured by negatively charged electrodes (collecting plate). Through this process, the solid particle content in the exhaust gas from waste combustion can be eliminated. Therefore, this final project involves the development of an electrostatic precipitator prototype aimed at reducing environmental pollution, particularly air pollution.